INTRODUCTION TO THE WORLD OF STOCK INVESTMENT AMONG MILLENIAL CHILDREN IN SENIOR HIGH SCHOOL NEGERI 1 STABAT - Arnita, Vina; Siregar, Oktarini Khamilah; Aulia, Yurika; Suhut, Anwar (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Investment is still one of the most difficult things to do, especially for the younger generation, especially in investing in the capital market because many assume that investing in the capital market is difficult to do and requires large initial capital and the risk of the future. capital market investment is difficult to do and requires a large initial capital and a large future risk. Future risk. The IDX (Indonesia Stock Exchange) as the body in charge of problems in capital market investment in Indonesia launched the capital market investment in Indonesia launched a product in the form of an Investment Gallery created on campus with the aim of becoming the target of students. Campus with the aim of being the most potential target for students to become young investors and provide additional knowledge to residents around the campus as well as to provide additional knowledge to residents around the campus as well to start investing in the capital market, especially stocks and shares. The purpose of this research is to find out whether the existence of the Investment Gallery on the Gunadarma campus is a good idea. the existence of the Investment Gallery on the Gunadarma campus can increase student interest in investing in the capital market from a young age.